Want to do some investing ? - Bloomfield, Alan (Raton, New Mexico Raton Daily Range, 1974)
The library has a selection of materials published weekly, quarterly and annually printed Moody's Investors services, Inc. Twice weekly the library receives reports about stocks and the market from Moody's and places them in three ring binders.
Article in the Raton Daily Range with a photo attached.
Master list item # 66
File location is in the Raton File Cabinet drawer 3
Keywords: Reporter Raton Daily Range -- Raton, New Mexico; Moody's Investors services, Inc. -- Raton, New Mexico